C-Reactive Protein at Hospital Discharge and 1-Year Mortality in Acute Infective Endocarditis: A Prospective Observational Study - Lin, Yaowang; Chen, Jie; Liao, Bihong; Bei, Weijie; Wang, Yongshun; Sun, Xin; Yuan, Jie; Dong, Shaohong (Frontiers in Cardiovascular Medicine, 2021)
Background: An accurate biomarker at hospital discharge is needed to identify patients with acute infective endocarditis (IE) who are at high risk of mortality. This prospective observational study evaluated the prognostic value of C-reactive protein (CRP). Methods: Patients with acute IE (n = 343) and hospitalized at 2 university-affiliated medical centers from January 2014 to December 2019 were enrolled. Patients were categorized as having low or high CRP (n = 217 and 126, respectively) at hospital discharge according to the optimal cutoff (CRP = 6.5 mg/L) determined via receiver-operating characteristic curve analysis. The primary endpoint was all-cause death, from hospital discharge to 1 year. The secondary endpoint was the cumulative rate of rehospitalization or paravalvular abscess at 1 year. Results: At the 12-month follow-up, the mortality rate of the high-CRP group (21.43%) was significantly higher than that of the low-CRP group (2.76%, log-rank P < 0.0001). The multivariate regression analysis indicated that the high-CRP group had a higher excess mortality hazard risk (HR = 4.210; 95% CI: 2.210, 5.420; P < 0.001). The cumulative 1-year incidence of paravalvular abscess of the high-CRP group (11.90%) was significantly higher than that of the low-CRP (5.07%; P = 0.022). The cumulative rate of heart rehospitalizations of the 2 groups were similar (18.25% cf. 14.29%, P = 0.273). Conclusion: For hospitalized patients with acute IE, a high CRP at discharge suggests a poor prognosis for 1-year mortality and paravalvular abscess.